2021
DOI: 10.3390/ijerph18168299
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Sarcopenia among Older Adults Aged ≥65 Years Admitted to Daycare Centers of Taiwan: Using AWGS 2019 Guidelines

Abstract: Sarcopenia is a geriatric syndrome which is likely to cause disability, body unbalance, and mortality and thus can lead to heavy healthcare expenditure and caregiver burden. Although some studies have addressed the prevalence of sarcopenia for older adults, there are limited studies conducted in daycare centers. The present study aimed to (i) estimate the prevalence of sarcopenia and (ii) explore associated factors of sarcopenia and standing balance among older adults admitted to daycare centers in Taiwan. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 51 publications
4
37
1
2
Order By: Relevance
“…Second, the differences may be ascribed to the age of the sample. In the present study, the mean age of the sample (71.9 years old) was older than that in the study of Miura et al (2021) [ 17 ] and younger than that in the study of Chang et al (2021) [ 18 ]. Previous studies have suggested that older age groups were more likely to develop possible sarcopenia [ 9 , 13 , 16 ].…”
Section: Discussioncontrasting
confidence: 76%
See 4 more Smart Citations
“…Second, the differences may be ascribed to the age of the sample. In the present study, the mean age of the sample (71.9 years old) was older than that in the study of Miura et al (2021) [ 17 ] and younger than that in the study of Chang et al (2021) [ 18 ]. Previous studies have suggested that older age groups were more likely to develop possible sarcopenia [ 9 , 13 , 16 ].…”
Section: Discussioncontrasting
confidence: 76%
“…One plausible explanation is that the mean BMI of 26.9 kg/m 2 in the present study was greater than that of 19.4 kg/m 2 in the study of Miura et al (2021) for older adults with possible sarcopenia [ 17 ]. Previous studies indicated that higher BMI had a protective effect against possible sarcopenia [ 9 , 16 , 18 ]. Furthermore, our findings seem to echo a cross-sectional study of older adults in Switzerland by Bertschi et al (2021), indicating that low BMI (with a mean of 25.6 kg/m 2 ) was not associated with probable sarcopenia according to new criteria of the European Working Group on Sarcopenia in Older People 2 [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations